Water and Wastewater Services in the Danube Region : Bulgaria Country Note - World Bank (Washington, DC, 2015)
To evaluate and reflect the sustainability of services in the region, an overall sector sustainability assessment was done taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess the sector sustainability is included in the Annex of the State of the Sector Regional Report from the Danube Water Program. The outcomes of this assessment for Bulgaria’s water sector are presented, which also shows average and best practices in the Danube region. The Bulgarian sector sustainability score is 66, which is just above Danube average sustainability of 64. The assessment shows that, on average, the country performs well in terms of access to piped water, staffing level, and nonrevenue water. The main deficiencies of Bulgaria’s water sector identified through the sector sustainability assessment are operating cost coverage, investment level, and customer satisfaction level.